Groundwater suitability for irrigated agriculture in alluvial Bengal delta plain: a review - Md. Shajedul Islam; M. G. Mostafa (Institute of Advanced Engineering and Science, 2021)
Groundwater is a vital source of irrigation and domestic purposes in Bangladesh, and hence, it must satisfy the water quality guidelines. The study has selected 11 districts of Bangladesh and collected secondary data regarding the irrigation water quality of groundwater. Several irrigation water indices, such as soluble sodium percentage (SSP), sodium adsorption ratio (SAR), magnesium adsorption ratio (MAR), residual sodium carbonate (RSC), Kelly’s ratio (KR), permeability index (PI), and irrigation water quality (IWQ) index are applied to evaluate irrigation water quality. According to IWQindex, the results showed 25.5% of water samples fell in a highly suitable water type, whereas 33.5% exhibited a low suitability type, and the remaining 41% showed medium suitability for irrigation purposes. The values of SAR, SSP, RSBC, and MAR indices showed that about 31-64% of water samples were very good, whereas 5-20% were very poor for the same purpose. The results of TDS, EC, and total hardness showed good results as 88-93% of water samples fell in fair to excellent quality. The salinity hazard was found in the groundwater of coastal areas and was completely unfit for irrigation. The study findings would help for improving the management of the groundwater resources for agricultural purposes in Bangladesh.